High-voltage pH differential vanadium-hydrogen flow battery. (December 2018) - Weng, Guo-Ming; Li, Chi-Ying Vanessa; Chan, Kwong-Yu
Abstract: We report a rechargeable pH differential vanadium-hydrogen (V-H2 ) flow battery with a practical open circuit voltage of 1.93 V and a discharge voltage of 1.73 V. This value is among the highest reported values for rechargeable flow batteries with aqueous electrolytes to date. This proposed V-H2 system demonstrates relatively high efficiencies in voltage (89%), Coulomb (85%) and energy (75%). Moreover, V-H2 system shows a high experimental specific energy of 135.6 Wh kg −1 which is about 2.6 times higher than that of the state-of-the-art all vanadium redox flow battery. This work offers new opportunities to develop high-specific-energy energy storage technologies. Graphical abstract: It is the first paper to report a scalable pH differential rechargeable vanadium-hydrogen (V-H2 ) flow battery with very high cell voltage and specific energy among all rechargeable flow batteries. Highlights: A scalable and high-voltage pH differential vanadium-hydrogen flow battery was demonstrated. This novel V-H2 flow battery has a theoretical specific energy of 300 Wh kg −1 . The V-H2 system showed relatively good reversibility and efficiencies.